TEACHERS’ PROFESSIONAL DEVELOPMENT IN KWARA STATE BASIC SCHOOLS: IMPLICATION ON INTERNAL EFFICIENCY - Habibat Abubakar Yusuf; Abdulkareem Rasaq Lanre (Proceedings of The ICECRS, 2016)
This paper investigated teachers’ professional development in Kwara state basic schools and its implications on internal efficiency. The purpose of the study is to investigate the level of teachers’ professional development in Kwara state basic schools and examine its implications on internal efficiency of the schools. Two research questions and one hypothesis were set to guide the study. Descriptive research design was adopted for the study. Secondary data were collected on teachers’ professional development while researchers’- designed questionnaire was used to collect data on internal efficiency. The questionnaires were given to 315 head teachers in Kwara state basic schools in Kwara State. Percentage was used to answer the research questions while Pearson’s moment correlation statistic formulated. The findings of the study included that; there is low level of teacher professional development in Basic schools in Kwara state; the internal efficiency of basic schools in Kwara state is low; and there is significant relationship between teachers’ professional development and internal efficiency of basic schools in Kwara state. Based on the findings, it was recommended that kwara state government should enhance adequate teachers’ professional development through adequate training, scholarship, more funding to ensure internal efficiency.